2016
DOI: 10.1186/s12940-016-0166-4
|View full text |Cite
|
Sign up to set email alerts
|

The association between ambient temperature and preterm birth in Shenzhen, China: a distributed lag non-linear time series analysis

Abstract: BackgroundA few studies have examined the association between ambient temperature and preterm birth (PTB), and the results have been inconsistent. This study explored the association between ambient temperature and PTB in Shenzhen, China.MethodsData of daily singleton PTB, air pollution and meteorological variables from 2005 to 2011 were collected in Shenzhen. A distributed lag non-linear model (DLNM) was used to investigate the association of the low and high temperatures (1st, 5th, 95th, and 99th percentiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 52 publications
1
47
1
Order By: Relevance
“…Table 1 shows study characteristics and whether heat exposure had a significant effect on the adverse outcomes examined within individual studies. Of the outcomes under investigation, preterm birth was the most common, investigated in 17 studies [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Preterm birth was defined as births occurring at less than 37 weeks of gestational age with a lower margin of 20 weeks, 22 weeks, or undefined in the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows study characteristics and whether heat exposure had a significant effect on the adverse outcomes examined within individual studies. Of the outcomes under investigation, preterm birth was the most common, investigated in 17 studies [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Preterm birth was defined as births occurring at less than 37 weeks of gestational age with a lower margin of 20 weeks, 22 weeks, or undefined in the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Heat was significantly correlated with increased risk or rate of preterm birth in 15 of 17 studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 34 ]; two studies found no significant effect [ 18 , 33 ]. A protective effect was demonstrated in Shenzhen, China for extreme heat exposure and preterm birth [ 30 ]. This result was in opposition to the other 13 studies and specifically to a study conducted in nearby Guangzhou [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…We considered that this may be due, at least in part, to behavioral changes. Under extremely high temperatures, mothers are more likely to attempt to mitigate exposure, including altering clothing, drinking fluids, or using air conditioning (Carolan-Olah and Frankowska 2014; Liang et al 2016). Such adjustments may offset some of the harmful effects of very intense heatwaves.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have usually used a series of temperature thresholds (absolute or percentiles) and durations to define heatwaves (Xu et al 2016). In our study location, some previous studies (He et al 2016;Liang et al 2016) evaluated high-temperature exposure and PTB, but the duration of hot days was not considered in their studies. Therefore, no clear evidence on appropriate absolute temperatures was available for us to define heatwaves.…”
Section: Heatwave Exposure Assessmentmentioning
confidence: 99%
“…The annual average temperature is 23.0 ∘ C, the average low temperature is 15.4 ∘ C in January, and the average maximum temperature is 28.9 ∘ C in July [38]. The mean annual total precipitation is 1933.3 mm, with the rainy season extending from April to September.…”
Section: Study Area the City Of Shenzhen Is Located Between 113mentioning
confidence: 94%